Phenotypic and Genotypic Analysis of Antimicrobial Resistance in Mycoplasma hyopneumoniae Isolated from Pigs with Enzootic Pneumonia in Australia - Raziallah Jafari Jozani; Mauida F. Hasoon Al Khallawi; Hanh Thi Hong Nguyen; Majed H. Mohammed; Kiro Petrovski; Yan Ren; Darren Trott; Farhid Hemmatzadeh; Wai Yee Low (Pathogens, 2024)
Mycoplasma hyopneumoniae, an important cause of enzootic pneumonia in pigs in many countries, has recently been shown to exhibit reduced susceptibility to several antimicrobial classes. In the present study, a total of 185 pig lung tissue samples were collected from abattoirs in Australia, from which 21 isolates of M. hyopneumoniae were obtained. The antimicrobial resistance profile of the isolates was determined for 12 antimicrobials using minimum inhibitory concentration (MIC) testing, and a subset (n = 14) underwent whole-genome sequence analysis. MIC testing revealed uniformly low values for enrofloxacin (≤1 μg/mL), florfenicol (≤8 μg/mL), lincomycin (≤4 μg/mL), spectinomycin (≤4 μg/mL), tetracycline (≤0.5 μg/mL), tiamulin (≤2 μg/mL), tildipirosin (≤4 μg/mL), tilmicosin (≤16 μg/mL) tulathromycin (≤2 μg/mL), and tylosin (≤2 μg/mL). Higher MICs were observed for erythromycin (MIC range: 16–32 μg/mL), gamithromycin, and tilmicosin (MIC range of both: 32–64 μg/mL). Whole-genome sequencing of the isolates and additional screening using mismatch amplification mutation assay PCR did not identify any known genetic resistance markers within 23S rRNA (macrolides), DNA gyrase A, and topoisomerase IV genes (fluoroquinolones). The WGS data also indicated that the Australian M. hyopneumoniae isolates exhibited limited genetic diversity and formed a distinct monophylectic clade when compared to isolates from other countries. These findings indicate that Australian M. hyopneumoniae likely remains susceptible to the major antimicrobials used to treat enzootic pneumonia in pigs and have evolved in isolation from strains identified in other pig-producing countries.